Comparison of Application Value of Different Radiation Dose Evaluation Methods in Evaluating Radiation Dose of Adult Thoracic and Abdominal CT Scan - He, Jimin; Dong, Guanwei; Deng, Yi; He, Jun; Xiu, ZhiGang; Feng, Fanzi (Frontiers in Surgery, 2022)
Objective: To explore the differences among volumetric CT dose index (CTDIvol), body-specific dose assessment (SSDEED) based on effective diameter (ED) and SSDEWED based on water equivalent diameter (WED) in evaluating the radiation dose of adult thoracic and abdominal CT scanning. Methods: From January 2021 to October 2021, 100 patients with enhanced chest CT scan and 100 patients with enhanced abdomen CT scan were collected. According to body mass index (BMI), it can be divided into groups A and D (BMI<20kg/m2), groups B and E (20kg/m2≤BMI≤24.9kg/m2) and groups C and F (BMI>24.9kg/m2). The CTDIvol, anteroposterior diameter (AP), left and right diameter (LAT) of all patients were recorded, and the effective diameter (ED), water equivalent diameter (WED), conversion factor (fsize,ED), (fsize,WED), SSDEED and SSDEWED were calculated. Compare the differences between different groups. Results: The AP, LAT, ED and WED of groups B, E, C and F were higher than those of groups A and D, and those of groups C and F were higher than those of groups B and E (P<0.05). The fsize,ED, fsize,WED of groups B, E, C and F are lower than those of groups A and D, and those of groups C and F are lower than those of groups B and E (P<0.05). CTDIvol, SSDEED and SSDEWED in groups B, E, C and F are higher than those in groups A and D, and those in groups C and F are higher than those in groups B and E (P<0.05). In the same group, patients with chest and abdomen enhanced CT scan have higher SSDEWED and SSDEED than CTDIvol, and patients with chest enhanced CT scan have higher SSDEWED than SSDEED, and patients with abdomen enhanced CT scan have higher SSDEED than SSDEWED (P<0.05). Conclusion: Compared with CTDIvol and ED-based SSDEED, WED-based SSDEWED can better consider the difference of patients' body shape and attenuation characteristics, and can more accurately evaluate the radiation dose received by patients with different body shapes during chest and abdomen CT scanning.